Laboratory diagnostics in COVID-19: what we know so far - Zakariah, Siti Zulaikha; Tengku Jamaluddin, Tengku Zetty Maztura; Mahayidin, Hasni; Dahari, Zuraihan; Ibrahim, Rosni (Ibn Sina Medical College, 2020)
COVID-19 took the world by storm in early 2020 which rapidly escalated to a pandemic of unprecedented proportions. Containment of the outbreak requires a robust public health system of surveillance, contact tracing and laboratory preparedness. Technological advancement in molecular diagnosticshas helped identify patients in the initial stages of the outbreak. RT-PCR remains the gold standard in COVID-19 testing. However, as the pandemic continues, there is need for rapid and point of care tests (POCT) for mass screening and rapid decision making. Current serological tests and POCT have high sensitivity but need to be interpreted with caution. This review aims to discuss current laboratory tests available for the diagnosis of COVID-19.